A redescription of the appendicular skeleton of Squalus acanthias (Elasmobranchii: Squaliformes: Squalidae). (24th June 2021) - C. B. da Silva, João Paulo; B. Vaz, Diego F.
Abstract: The anatomy of Squalus acanthias has been explored and investigated for the past 150 years. Despite being a relatively well‐known species, some anatomical inaccuracies on the paired fins persist throughout the literature, such as the presence of suprascapular cartilages and the morphology of the articular region of the pectoral fin. This study reassesses and provides new descriptions of the paired fins of Squalus acanthias, including comparisons with other representatives of Squalidae, aimed to expand the anatomical information of these species. All examined species of Squalus have two sites in the scapulocoracoid for the articulation of the pectoral basals: one facet articulating with the propterygium and a condyle for the mesopterygium (or both meso‐ and metapterygium). Additionally, the scapulocoracoid does not have a scapular process. Squalus acanthias is unique for having a series of barrel‐shaped elements in the anterior region of the scapula. These elements are lacking in all other examined species of Squalus and Cirrhigaleus (and sharks in general) and are likely an autapomorphy of S .  acanthias .